The English Course Management at English Cafe in Developing Students’ Speaking Skills - Nur Awaliyah (TEKNOSASTIK, 2021)
The objectives of this study are to find out the managements of English course and to find out what management is used in developing speaking skills. This English course used the concept of a cafe to attract students or university students. The concept of this course in an attraction in itself. The methodology of this research was qualitative research especially case study. The subjects of this research are manager, staffs, and chefs at English cafe Salatiga. The techniques of collecting data were observation, interview and documentation. the data from observation was to find out what kinds of management used in the learning process and to know how to apply its in English cafe Salatiga. The validity of data technique is triangulation by source and technique. The results obtained from this study: 1) the management of English course program at English cafe Salatiga conducted by several stages, there are planning administration and academic, organizing the management through organizational structure, motivating the English course program by implementing private, regular, online and TOEFL program, conforming through personal reinforcement by manager, evaluating the teaching learning, marketing, and administration, and the last was developing English course program. 2) The course management emphasized in developing speaking skills through learning design, strategies, and learning program.Keywords: speaking, English Course, English cafe